1999
DOI: 10.1118/1.598763
|View full text |Cite
|
Sign up to set email alerts
|

Spectra and air-kerma strength for encapsulated 192Ir sources

Abstract: The photon spectra in vacuum around four types of 192Ir HDR brachytherapy sources are calculated using the Monte Carlo code EGS4 and the most recent spectral information on 192Ir decay. The air-kerma strengths per unit activity are calculated based on the photon fluence around a bare 192Ir source and around each of four types of encapsulated sources using recent mass energy-absorption coefficients. For the full spectrum the bare vs encapsulated difference is up to 23% due to the large air-kerma contribution fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 9 publications
6
71
0
Order By: Relevance
“…Comparison of calculated air kerma strengths per unit activity, S k /A with published data. The cutoff energies of photon fluence spectra in the parenthesis of the last two columns were 11.3 keV and 60 keV for Borg and Rogers (13), and 60 keV for Büermann et al (14). The values of Borg and Rogers were averaged at several distances from 2 to 50 cm Hereafter, all dose rates were normalized at the air kerma strength of 4.082 ϫ 10 4 U, which corresponds to an apparent activity of 10 Ci.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of calculated air kerma strengths per unit activity, S k /A with published data. The cutoff energies of photon fluence spectra in the parenthesis of the last two columns were 11.3 keV and 60 keV for Borg and Rogers (13), and 60 keV for Büermann et al (14). The values of Borg and Rogers were averaged at several distances from 2 to 50 cm Hereafter, all dose rates were normalized at the air kerma strength of 4.082 ϫ 10 4 U, which corresponds to an apparent activity of 10 Ci.…”
Section: Resultsmentioning
confidence: 99%
“…The photon fluence spectrum (at 5 keV intervals) at 100 cm along the transverse axis was scored in a 0.5-cm-thick and 0.5-mm-high cylindrical voxel positioned symmetrically about the source axis. As [20,21] in their study on the calculation of fluence spectra and air-kerma strength of 192 I sources, the fluence spectrum was subsequently converted to air-kerma per initial photon (Gy/initial photon) by use of the mass-energy-absorption coefficient of air [22]. The authors utilized the EGS4-based [23] FLURZ user-code in their study.…”
Section: Monte Carlo Calculationsmentioning
confidence: 99%
“…(7). Borg and Rogers 9 found that there is no significant difference between the spectra in-air and in-vacuum.…”
Section: Iic Seven-distance Technique Overviewmentioning
confidence: 99%